A STUDY ON THE IMPLEMENTATION OF GST ON OPERATIONAL EFFICIENCY OF RETAILERS IN UTTAR PRADESH (International Journal of Food and Nutritional Sciences, 2022)
The implementation of the Goods and Services Tax (GST) in India on July 1, 2017, signified a significant transformation in the nation's taxation system